2014
DOI: 10.1158/1055-9965.epi-14-0700
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroid Hormone Metabolism in Relation to Risk of Aggressive Prostate Cancer

Abstract: Background: The combined action of androgens and estrogens-specifically their balance-may play a role in prostate carcinogenesis, but existing evidence is sparse and inconsistent. We investigated associations between serum sex steroid hormones, including estrogen metabolites, and risk of aggressive prostate cancer.Methods: In a case-control study nested within the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial cohort, we measured serum estrone, estradiol, and 13 estrogen metabolites, in the 2-, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
2
20
0
1
Order By: Relevance
“…There are various core regulatory factors and pathways in prostate cancer associated pathways ( hsa05215 ). Steroid hormone biosynthesis has been reported to contribute to the metastasis of prostate cancer and interacts with the specific oncogene of pancreatic cancer AR , implying its core role for the prostate associated pathways that we have predicted [51, 52]. According to recent publications, such core pathway of the steroid hormone biosynthesis may also contribute to pancreatic cancer, revealing the underlying relationships between prostate cancer associated pathways (as we have predicted, hsa05215) and pancreatic cancer [53, 54].…”
Section: Resultsmentioning
confidence: 98%
“…There are various core regulatory factors and pathways in prostate cancer associated pathways ( hsa05215 ). Steroid hormone biosynthesis has been reported to contribute to the metastasis of prostate cancer and interacts with the specific oncogene of pancreatic cancer AR , implying its core role for the prostate associated pathways that we have predicted [51, 52]. According to recent publications, such core pathway of the steroid hormone biosynthesis may also contribute to pancreatic cancer, revealing the underlying relationships between prostate cancer associated pathways (as we have predicted, hsa05215) and pancreatic cancer [53, 54].…”
Section: Resultsmentioning
confidence: 98%
“…We identified hormone-related genes through a search of both the PubMed/Gene database and also the Kyoto Encyclopedia of Genes and Genomes (KEGG) catalog gene search tool using the terms “sex steroid hormone” or “hormone” or “testosterone” or “androgen” or “estrogen” in the keyword search. In addition, we sought information through a search of recent (last 5 years) topical literature reviews or original research studies evaluating the sex steroid hormone pathway to learn of common ways of identifying genes along this pathway (2427). We excluded SNPs with a minor allele frequency less than 5% to allow for robust analysis of interactions between genetic loci and pesticide exposures.…”
Section: Methodsmentioning
confidence: 99%
“…Another study reported that serum E1, E2 and E1-S were commonly elevated in men with highgrade localized PCa (Giton et al 2008). Finally, others have reported the estrogen:androgen ratio is inversely related to the risk of aggressive PCa (Black et al 2014).…”
Section: Clinical Prognostic Value Of Serum Sex Steroids As Biomarkermentioning
confidence: 95%